(untitled) (Journal of the College of Basic Education, 2022)
Sufism has played a great way in caring for the family and saving it from the misguided and destructive thought of the Islamic society and working to raise the generation according to correct Islamic foundations that adopt the Noble Qur’an as a thought, the hadith and the Muhammadan biography as a method and we follow the recommendations of the companions as a program to enlighten the mind and heart The thought of Sufism has contributed to spreading security, morals, culture, moderation, humility, equality, respect for opinions and theories, and holding oneself and human beings accountable for mistakes, sins and abominations. From here, we will discuss in this study the impact of Islamic mysticism in building a moderate society and producing ideal children, taking the thought of Imam Al-Ghazali and Ibn Arabi in this field as a model. The nature of the study necessitated that we divide it into two sections, in the first section we dealt with Imam Al-Ghazali, may God have mercy on him, and social education, while we devoted the second section to talk about the Andalusian Sufi Muhyiddin Ibn Arabi and his social guidance, adopting the historical, analytical, descriptive method to reach the desired goals of the study and by referring to the sources and references Related